Electrochemical and Mechanistic Study of Reactivities of α-, β-, γ-, and δ-Tocopherol toward Electrogenerated Superoxide in N,N-Dimethylformamide through Proton-Coupled Electron Transfer - Tatsushi Nakayama; Ryo Honda; Kazuo Kuwata; Shigeyuki Usui; Bunji Uno (MDPI AG, 2021)
Scavenging of superoxide radical anion (O2•−) by tocopherols (TOH) and related compounds was investigated on the basis of cyclic voltammetry and in situ electrolytic electron spin resonance spectrum in N,N-dimethylformamide (DMF) with the aid of density functional theory (DFT) calculations. Quasi-reversible dioxygen/O2•− redox was modified by the presence of TOH, suggesting that the electrogenerated O2•− was scavenged by α-, β-, γ-TOH through proton-coupled electron transfer (PCET), but not by δ-TOH. The reactivities of α-, β-, γ-, and δ-TOH toward O2•− characterized by the methyl group on the 6-chromanol ring was experimentally confirmed, where the methyl group promotes the PCET mechanism. Furthermore, comparative analyses using some related compounds suggested that the para-oxygen-atom in the 6-chromanol ring is required for a successful electron transfer (ET) to O2•− through the PCET. The electrochemical and DFT results in dehydrated DMF suggested that the PCET mechanism involves the preceding proton transfer (PT) forming a hydroperoxyl radical, followed by a PCET (intermolecular ET-PT). The O2•− scavenging by TOH proceeds efficiently along the PCET mechanism involving one ET and two PTs.